Dendrimer‐Based Signal Amplification of Click‐Labelled DNA in Situ. (24th July 2017) - Raddaoui, Nada; Stazzoni, Samuele; Möckl, Leonhard; Viverge, Bastien; Geiger, Florian; Engelke, Hanna; Bräuchle, Christoph; Carell, Thomas
Abstract: The in vivo incorporation of alkyne‐modified bases into the genome of cells is today the basis for the efficient detection of cell proliferation. Cells are grown in the presence of ethinyl‐dU (EdU), fixed and permeabilised. The incorporated alkynes are then efficiently detected by using azide‐containing fluorophores and the Cu I ‐catalysed alkyne–azide click reaction. For a world in which constant improvement in the sensitivity of a given method is driving diagnostic advancement, we developed azide‐ and alkyne‐modified dendrimers that allow the establishment of sandwich‐type detection assays that show significantly improved signal intensities and signal‐to‐noise ratios far beyond that which is currently possible. Abstract : Finding a needle in a haystack : A new method to detect proliferating cells in situ by using multiple consecutive click reactions with dendrimeric molecules and clickable dyes is presented. These assays have outstanding sensitivities; signal intensities and signal‐to‐noise ratios are far better than those obtained by techniques that are currently available. EdU=ethinyl‐dU.